Crime at Sea: A Global Database of Maritime Pirate Attacks (1993–2020). (30th August 2021) - Benden, Paul; Feng, Alan; Howell, Christopher; Dalla Riva, Giulio Valentino
This dataset contains information from more than 7, 500 maritime pirate attacks that took place between January 1993 and December 2020, as well as country indicator data for the same time period. The pirate attack data was collected from the International Maritime Bureau (IMB), tidied, and augmented with geospatial data. The country indicator data was gathered from a variety of sources, notably The World Bank. The data is contained in Comma Separated Value (CSV) files. The reuse potential includes its use by anti-piracy organisations and researchers, as well as commercial businesses, in the understanding and prevention of maritime piracy. This dataset is available through Zenodo and Github.